PEMBERDAYAAN LINGKUNGAN ANAK - Suryadi Suryadi (AWLADY : Jurnal Pendidikan Anak, 2016)
AbstractFamily Educational design could impact child personality in their life. The family that set up education in democratic circumstance makes children more stable in manner and behaviour, children that are educated in authoritarianism situation tent to aggressive. Family that set up in permissive circumstance make them more aggressive. The research result could be interpreted that we have to evaluate three educational environments, namely: family, school and community (peer groups). We have to design those environments which could support the child in their psychology development phase. The other is IT tools, the one relatively newest educational institution that also could impact child behaviour. Family empowerment is one of the best solutions in handling and facing modern and globalization era.Key words: family empowerment, child education, educational environment